PSYCHO-SOCIO AND RE MAND HOME RELATED FACTORS AS DETERMINANTS OF RECIDIVISM AMONG JUVENILE OFFENDERS IN OYO AND LAGOS STATES, NIGERIA (2017)
Juvenile involvement in antisocial activities after reformation is on the increase in Nigeria, largely due to ineffective rehabilitation. Most juvenile offenders relapse into recidivism as a result of public rejection and realities of meeting up with their daily living, because they are early school leavers who had not learnt any trade before they were sent for correction. Previous studies on juvenile recidivism focused on juvenile justice administration, empowering youths in remand homes against risk taking behaviour with little emphasis on psycho-socio and remand home related factors predisposing them to recidivism. This study, therefore, investigated psycho-(Self-esteem), Socio-(family background, peer influence, media content) and remand home related factors (deviant peers, hard treatment in the correctional centre, lack of care), as determinants of recidivism among juvenile offenders in Oyo and Lagos states, Nigeria. The study was guided by differential association, strain and labelling theories, while descriptive survey design was adopted. Respondents were: 150, 115 and 192 inmates from Ibadan (Oyo State), Idi Araba and Oregun (Lagos State), making a total of 457 juvenile offenders. Family background (r=0.83); Media contents (r=0.85); Peer influence (r=0.75); Remand home factors (r=0.73); Recidivism (r=0.73); Self-esteem (r=0.82) scales were used. Data collected were analysed using descriptive statistics, Pearson product moment correlation and Multiple regression at 0.05 level of significance. Six sessions of focus group discussion were conducted with juvenile offenders and were content analysed. Sixty-one percent of juvenile offenders were boys, while 39.39% of the juvenile offenders were females. Family background (r=0.45), peer influence (r=0.54), self-esteem (r=-0.05) remand home factors (r=0.13), media content (r=0.65) correlated significantly with recidivism. The F value ratio of the result (F(5.446)= 89.60; p<0.05) shows that there is composite contribution of independent variables on juvenile recidivism and jointly accounted for 49.6% of its variants. The relative contributions of family background to recidivism was not significant (β=.059) while Peer influence (β=.207), self-esteem (β=-225); Remand home factors (β=.088); media content (β=.525) significantly predicted recidivism. Juveniles’ family background, self-esteem, peer influence, remand home factors and media content contributed to juvenile recidivism. Family background, peer influence, media content, self-esteem and remand home factors contributed to juvenile recidivism in Oyo and Lagos States, Nigeria. Parents and other stake holders should check juveniles’ exposure to peer pressure and media utilisation to curb juvenile recidivism. Social Welfare officers and correctional psychologists should give priority to these factors while planning intervention and corrective programmes for the juveniles.